2019
DOI: 10.5897/jahr2019.0494
|View full text |Cite
|
Sign up to set email alerts
|

Medication belief, locus of control, and adherence among patients on highly active anti retro viral therapy in Lagos, Nigeria

Abstract: Anti-retro viral therapy (ART) is a lifelong treatment and its effectiveness depends critically both on the efficacy of the antiretroviral drugs against the virus and achieving a very high level of adherence (> 95%) to the medications. This study evaluated the relationship between medication beliefs, locus of control and adherence to ART among people living with HIV/AIDS (PLWHA) in Lagos. A cross-sectional descriptive study was conducted on 302 HIV/AIDS clients receiving Highly Active Anti-Retroviral Therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Also, those who were very concerned about the potential bad effects of the ART medicine were 1.3 times more likely to be non-adherence to ART than those who were less concerned. These results were consistent with other studies that revealed that beliefs in medicine are associated with compliance to ART [ 52 - 54 ]. Medicine beliefs, whether positive or negative, have an impact on medication usage.…”
Section: Discussionsupporting
confidence: 93%
“…Also, those who were very concerned about the potential bad effects of the ART medicine were 1.3 times more likely to be non-adherence to ART than those who were less concerned. These results were consistent with other studies that revealed that beliefs in medicine are associated with compliance to ART [ 52 - 54 ]. Medicine beliefs, whether positive or negative, have an impact on medication usage.…”
Section: Discussionsupporting
confidence: 93%